Tinjauan Terhadap Tindak Pidana Pencabulan pada Anak di Bawah Umur Berdasarkan Undang-Undang Perlindungan Anak - Leni Anggraeni; R. Rahaditya (Syntax Literate, 2023)
Various issues regarding criminal acts are increasingly increasing the number of cases and also the victims of criminal acts. Criminal acts that occur are caused by several factors, from the pressure of economic needs to conditions that endanger or injure victims both psychologically is sexual abuse, especially of children. Children should be a priority for parents, society and government because children who are still minors are still uder the protection of parents and the law in Indonesia, especially the Law on Child Protection which is clear in which children have their own rights, one of which is not to receive indecent treatnent such as criminal acts of decency. Sexual abuse itself has a definition as a form of action or action in expressing syahwatnya to others by force. The act of sexual abuse that is in the public spotlight today is the perpetrators who launch their actions on children. The occurrence of this act of sexual abuse is due to internal factors and also external factors. However, the acts of sexual abuse must still be processed by the law because it is included in criminal law and there must be sanstions and provisions for the verdict of the criminal case of this sexual abuse.